An Increasing Need for Productive and Stress Resilient Festulolium Amphiploids: What Can Be Learnt from the Stable Genomic Composition of Festuca pratensis subsp. apennina (De Not.) Hegi? - Kopecký, David; Harper, John; Bartoš, Jan; Gasior, Dagmara; Vrána, Jan; Hřibová, Eva; Boller, Beat; Ardenghi, Nicola M. G.; Šimoníková, Denisa; Doležel, Jaroslav; Humphreys, Mike W. (Frontiers in Environmental Science, 2016)
Genome composition of Festuca pratensis subsp. apennina (De Not.) Hegi, a tetraploid fescue species native to the tall forbs communities of south-eastern Europe at altitudes between 1100 and 2200m a.s.l. has been the subject of some debate by grass taxonomists. Our cytogenetic analyses including fluorescence in situ hybridisation with probes for genomic DNA and selected DNA repeats revealed the species to be allotetraploid and derived from interspecific hybridization between F. pratensis Huds., a species confined to grassland at lower altitudes, and a so far unknown Festuca species. Besides tetraploids, triploids and pentaploids were found growing in Alpine meadows in close association with F. pratensis subsp. apennina. Triploid cytotypes predominated at many sites in Switzerland and Romania, and in some localities, they were the only cytotypes observed. Cytogenetic analyses revealed the triploids to be hybrids between diploid F. pratensis and tetraploid Festuca pratensis subsp. apennina, while the pentaploid cytotypes originated from hybridization between F. pratensis subsp. apennina and hexaploid F. arundinacea Schreb., a closely-related species growing in a close vicinity to F. pratensis subsp. apennina. Parental genomes of F. pratensis subsp. apennina and of the triploid and pentaploid hybrids showed no evidence of homoeologous chromosome pairing and interspecific recombination, supporting previous observation of a disomic inheritance at meiosis, where chromosome pairing was restricted to bivalent associations. A hypothesis is presented that a chromosome pairing regulator(s), reported previously in other polyploid broad-leaved fescue species of the Festuca subg. Schedonorus, is present and functional in F. pratensis subsp. apennina. It is likely that a common ancestors’ genome that carries the chromosome pairing regulator(s) is present in all polyploid broad-leaved fescue species, and its acquisition was a key event that enabled speciation, and development of a polyploid series within Festuca. Identification of a functional chromosome pairing regulator capable of stabilizing advantageous genome combinations in hybrids within the Lolium-Festuca complex would greatly assist in development of stable Festulolium cultivars. Its expression within Festulolium amphiploid cultivars would assist strategies aimed at climate-proofing productive European grasslands to combat exposures to stress conditions.